Alexander Rich: In Memoriam. Issue 11 (November 2015) - Perrigue, Patrick M.; Erdmann, Volker A.; Barciszewski, Jan
Abstract : Rich's biggest discoveries were left-handed Z-DNA, the tertiary structure of tRNA, and that DNA and RNA strands could pair up. His discoveries provided the groundwork for our understanding of nucleic acid structure and consequently the development of the fields of molecular biology, biotechnology, and nanotechnology.